Bush ways : a bush-lover's wanderings on plain and range in central and eastern Australia. - Russell, Archer, 1881- (Sydney, : Australasian Publishing Co., 1944)
Mainly ornithological information; contains some comments on Aborigines and their life style in desert areas.
Keywords: Zoology -- Australia; Natural history -- Australia; Australia -- Description and travel; New South Wales (NSW); Northern Territory (NT)